Digital Quality Management in Islamic Education: A Framework for E-Learning Integrity and Religious Value Internalization - Rois Mahmudi; Siti Aimah (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study aims to analyze and develop a Digital Quality Management (DQM) framework for Islamic Educational Institutions to improve the quality of e-learning while strengthening the internalization of religious values. Using a qualitative case study approach, data was obtained through in-depth interviews with research subjects, including leaders of Islamic educational institutions, heads of curriculum departments, e-learning managers, teachers and students, participant observation, and documentation of policies, quality guidelines, academic reports, and digital archives. Data analysis followed the interactive model of Miles and Huberman, including reduction, presentation, and conclusion drawing, with validity ensured through triangulation of sources, methods, and observers. The results of the study formulated four pillars of digital quality management: the integration of uswah hasanah values in cyber risk management, the role of tafaqquh fiddin as a digital literacy strategy for students, the “sunnah fasting-based independent time audit” model for device self-regulation, and the effectiveness of “double certification” in ensuring teacher academic integrity. This research contributes practical operational guidelines for Islamic schools to ensure that technology functions as a reinforcement of religious identity, not merely as an administrative tool. Overall, this digital quality management framework holistically integrates the dimensions of technology, quality management, and Islamic values to address digital transformation in Islamic educational institutions.